Stinkbomb and Ketchup-Face and the badness of badgers - Dougherty, John (G.P. Putnam's Sons, 2017)
Stinkbomb and his sister, Ketchup-Face, with help from King Toothbrush Weasel, go on an adventure to recover the stolen contents of their piggybank from a gang of rascally badgers.